Anxiety levels of voluntary blood donors in the blood donor unit of PMI Yogyakarta City - Nur'Aini Purnamaningsih; Suwarno Suwarno; Muhammad Erwan Syah; Diah Nurpratami (Universitas 'Aisyiyah Yogyakarta, 2022)
Adverse events have an impact on the safety of blood donors and affect the interest in donating blood again. This adverse event is related to the anxiety experienced by blood donors. This study aims to determine the level of anxiety of voluntary blood donors after blood donation at the Blood Donor Unit PMI Yogyakarta City. This research is a descriptive research. The research instrument used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The population in this study were blood donors at the PMI Blood Donor Unit, Yogyakarta City. The sampling technique uses quota sampling. The sample in this study were voluntary blood donors as many as 100 people who met the requirements for blood donation. Requirements for blood donors include physically and mentally healthy, age 17-60 years, minimum weight 50 kg, hemoglobin 12.5-17 g/dl, blood pressure 110/70 mmHg to 150/90 mmHg, and for women who are not pregnant/ breastfeeding/menstruation. Data were analyzed descriptively and presented with tables. The results showed that the majority of voluntary blood donors in the Blood Donor Unit PMI Yogyakarta City did not have anxiety (93%). Mild anxiety is most common in the younger age group, female gender, higher education and university students. Building and increasing self-efficacy, providing a positive blood donation experience, and mechanisms to reduce the rate of vasovagal reactions are important things to do to reduce anxiety, prevent vasovagal reactions and maximize donor retention.